СТАБІЛІЗАЦІЯ НАПРУГИ КОНТАКТНОЇ МЕРЕЖІ ДЛЯ ПІДВИЩЕННЯ ЕНЕРГОЕФЕКТИВНОСТІ СИСТЕМИ ЕЛЕКТРИЧНОЇ ТЯГИ ПОСТІЙНОГО СТРУМУ - Тугай , Д.В.; Жемеров, Г.Г. (Інститут електродинаміки НАН України, Київ, 2018)
The possibility of increasing the efficiency of the DC electric rail traction system due to the use of active rectifiers – voltage sources on traction substations for voltage stabilization on the electric rolling stock pantograph is substantiated. The calculation formulas allowing determining the trajectories of the voltage stabilization on the rolling stock pantograph depending on the position of the electric train are obtained. These formulas allow us to determine for the two stabilization methods – «synchronous» and «asynchronous».  References 5, figures 4, table 1.